RISK FACTORS OF ANEMIA IN ADOLESCENT GIRLS IN WETLAND AREAS: A STUDY IN SOUTH KALIMANTAN - Yulidasari , Fahrini; Solechah, Siti Aisyah; Setiawan , Muhammad Irwan; Anhar, Vina Yulia; Noor, Ihya Hazairin; Santoso, Izal Puji; Fatimah, Husnul (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Anemia in adolescent girls is a global and national public health problem that is receiving increasing attention due to the high nutritional needs during growth and iron loss during menstruation. Preliminary data from wetland areas, particularly in Sungai Alang Village, Banjar Regency, shows a prevalence of anemia of 23.54%. This study aims to analyze risk factors associated with anemia in adolescent girls, including age, education level, nutritional knowledge, dietary behavior, and nutritional status based on Mid-Upper Arm Circumference (MUAC) and Body Mass Index (BMI). Method: This study used an observational analytical design with a cross-sectional approach in 50 adolescent girls aged 12–24 years selected through purposive sampling. Data were obtained through questionnaires and hemoglobin level measurements using an Hb meter. Analysis was performed using Spearman's rho correlation test and multivariate linear regression. Result: The results showed a prevalence of anemia of 34%, exceeding the threshold for a moderate public health problem according to the WHO. Bivariate analysis found a significant negative correlation between age and Hb levels (r=-0.405; p=0.004) and a significant positive correlation between MUAC and Hb levels (r=0.373; p=0.008). Meanwhile, knowledge, BMI, and dietary behavior did not show a significant correlation. Multivariate analysis identified age (β=-0.459; p=0.000), MUAC (β=0.599; p=0.000), and BMI (β=-0.354; p=0.033) as significant independent predictors. Conclusion: The results confirmed that anemia in adolescent girls is influenced by physiological factors and anthropometric status, while knowledge and dietary behavior do not play a direct role. Therefore, preventive interventions need to be carried out holistically through supplementation, targeted nutrition education, and other supporting health programs.